2009
DOI: 10.1051/parasite/2009163235
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofCryptosporidiumoocysts in green mussels (Perna viridis) from shell-fish markets of Thailand

Abstract: Summary :Mussels filter large volumes of water and can concentrate pathogenic organisms, which may act as potential vehicles of transmission to the consumer. A survey study was carried out to investigate the presence of Cryptosporidium protozoan parasites in green mussels (Perna viridis), the smussles pecies most destined for consumption in Thailand. In total, 56 samples were examined from Bangkok (n = 24) and Samut Prakan (n = 32) a wholesale shell-fish markets located at the mouth of the Chao Phraya River. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Cryptosporidium oocysts can be dispersed on pasture directly by animals or by spreading the manure on pasture (Sischo et al, 2000), propagating infection over vast areas or in surface water. Our results support the hypothesis that humans may receive Cryptosporidium oocysts by contamination of food and drinking water (Srisuphanunt et al, 2008(Srisuphanunt et al, , 2009(Srisuphanunt et al, , 2010 or domestic animals and these data represent a substantial report of HIV/AIDSconfirmed cases of cryptosporidiosis in Thailand. It is not excluded that the course of cryptosporidiosis in the investigated patients depends on different Cryptosporidium subtypes and this should be a subject of future studies to confirm individual differences or correlations of symptoms in the affected persons.…”
Section: Discussionsupporting
confidence: 78%
“…Cryptosporidium oocysts can be dispersed on pasture directly by animals or by spreading the manure on pasture (Sischo et al, 2000), propagating infection over vast areas or in surface water. Our results support the hypothesis that humans may receive Cryptosporidium oocysts by contamination of food and drinking water (Srisuphanunt et al, 2008(Srisuphanunt et al, , 2009(Srisuphanunt et al, , 2010 or domestic animals and these data represent a substantial report of HIV/AIDSconfirmed cases of cryptosporidiosis in Thailand. It is not excluded that the course of cryptosporidiosis in the investigated patients depends on different Cryptosporidium subtypes and this should be a subject of future studies to confirm individual differences or correlations of symptoms in the affected persons.…”
Section: Discussionsupporting
confidence: 78%
“…in HIVinfected patients, in cattle, and in food (green mussels) have been already reported from Thailand (Uga et al 2000;Gatei et al 2002;Saksirisampant et al 2002;Tiangtip and Jongwutiwes 2002;Nuchjangreed et al 2008;Srisuphanunt et al 2009), no outbreaks of waterborne cryptosporidiosis or giardiasis have been reported in the country, and they could not be included in the systematic review covering all reports worldwide of waterborne protozoan outbreaks by Karanis et al (2007). No data exist regarding protozoan parasite concentrations in wastewaters or in reuse and recycling of wastewaters for agriculture and industry and in backwash water from drinking water treatment plants in Thailand.…”
Section: Dicussionmentioning
confidence: 77%
“…Cryptosporidium and Giardia parasites have been detected in approximately 13% of oysters in The Netherlands (81) and 40 to 50% in Norway (78). These two parasites have also been detected on rare occasions in edible mollusks in Asia (84) and Africa (73).…”
Section: Occurrence Of Giardia Cryptosporidium and Toxoplasma Parasmentioning
confidence: 99%
“…Addition ally, samples can be sieved at 45 to 150 pm to remove large aggregates (56). Homogenates are then often mixed with PBS and diethyl ether (at a 2:1 ratio) in order to remove lipid materials from the samples (12,31,35,36,39,47,55,84). Samples may be further purified by flotation on continuous or discontinuous gradients of sucrose (33,57,67,71,75,89) or cesium chloride (40,42,63,67) solutions.…”
Section: Detection and Characterization Of Protozoan Pathogens In Molmentioning
confidence: 99%